1969
DOI: 10.4098/at.arch.69-18
|View full text |Cite
|
Sign up to set email alerts
|

The food of the roe deer

Abstract: A total of 46 rumens of roe-deer, Capreolus capreolus (Linnaeus, 1758) were examined over the course of four hunting seasons from 1963-1966. The material was obtained from part of the Pisz Forest ((53°43' N, 21°36' E), where the Pineto-V accinietum myrtilli and Pineto-Quercetum associations dominated. 178 species of plants were identified in the rumen contents. Seasonal variations were found in the food of roe-deer. Their basic food consists of the leaves and twigs of trees, shrubs and dwarf-shrubs. During spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
1

Year Published

1972
1972
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 1 publication
3
28
1
1
Order By: Relevance
“…Therefore, roe deer must have better exploited some plant species few in number but abundant, in the smaller microhabitats. One to 3 plant species were also dominanted in each roe deer sampled in Pinetum-Vaccinietum myrtilly and Pineto-Quercetum associations (Siuda et al, 1969). The small ruminants like roe deer rather need to remain stationary and economize on energy reserves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, roe deer must have better exploited some plant species few in number but abundant, in the smaller microhabitats. One to 3 plant species were also dominanted in each roe deer sampled in Pinetum-Vaccinietum myrtilly and Pineto-Quercetum associations (Siuda et al, 1969). The small ruminants like roe deer rather need to remain stationary and economize on energy reserves.…”
Section: Resultsmentioning
confidence: 99%
“…Within browse pine occured in high proportion in red and roe deer diet (27% and 35%, respectively). Red and roe deer consumed the similar proportion of pine during winter (Siuda et al, 1969;Gejbczyriska, 1980). Blair et al, (1977) have found that evergreen needles, browse leaves and twig tips were the most nutritious plants for white-tailed deer (Odocoileus virginianus).…”
Section: Resultsmentioning
confidence: 99%
“…In case of deer this food supply consists mainly of browse (Siuda, Żurowski B. Bobek & R. Dzięciołowskj & Siuda, 1969;Dzi^ciolo wski, 1970). The browse includes in principle the current growth of trees and shrubs remaining within the reach of animals (De Vos & Mosby, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Even though microscopic studies provide too low values of the real content of easily digested herbs in the food consumed regard to their short retention time of in the alimentary tract, their results always show a certain contribution of herbs to the stomach contents (Siuda et al, 1969;Ga are et al, 1977; Matu-ł a, unpubl.). The accurate determination of the proportions of food constituents in the roe-deer should however be performed on the basis of feeding experiments.…”
Section: Influence Of Food Composition On Energy Balance In Roe-deermentioning
confidence: 99%